Hubungan Tingkat Pengetahuan dan Sumber Informasi dengan Perilaku Personal Hygine Saat Menstruasi pada Remaja Putri Usia 14-19 Tahun di Desa Kuranji Tahun 2025 - Astawan, Wanda Januar; Irmayunita, Mia (Empiricism Journal, 2026)
Masa remaja ditandai perubahan fisik, emosional, dan psikologis, termasuk menstruasi pada remaja putri. Personal hygiene yang baik diperlukan untuk mencegah infeksi saluran reproduksi, infeksi saluran kemih, dan gangguan kesehatan lainnya. Namun, praktiknya masih rendah akibat keterbatasan pengetahuan dan akses informasi. Data Puskesmas tahun 2025 menunjukkan hanya 25% remaja putri di Desa Kuranji memahami pentingnya mengganti pembalut setiap 4–6 jam, sedangkan survei terhadap 7 remaja putri menemukan 5 orang belum menerapkannya dengan baik. Penelitian ini bertujuan mengetahui hubungan tingkat pengetahuan dan sumber informasi dengan perilaku personal hygiene saat menstruasi pada remaja putri di Desa Kuranji tahun 2025. Penelitian kuantitatif dengan pendekatan cross sectional ini melibatkan populasi 85 remaja putri dan sampel 46 responden yang dipilih melalui proportionate stratified random sampling. Kriteria sampel ialah telah mengalami menstruasi dan berusia 14-19 tahun. Data dikumpulkan menggunakan kuesioner dan dianalisis secara univariat serta bivariat dengan uji chi-square. Hasil menunjukkan 23,9% responden berpengetahuan baik dan 54,3% memiliki sumber informasi baik. Terdapat hubungan signifikan antara pengetahuan dan perilaku personal hygiene dengan p-value 0,001 (p < 0,05), serta antara sumber informasi dan perilaku dengan p-value 0,013 (p < 0,05). Pemerintah Desa Kuranji dan Puskesmas Perampuan disarankan menyelenggarakan edukasi kesehatan reproduksi yang terstruktur, berkelanjutan, dan mudah diakses bagi remaja. The Relationship Between the Level of Knowledge and Information Sources with Personal Hygine Behavior During Menstruation Among Adolescent Girls Aged 14-19 Years in Kuranji Village in 2025 Abstract Adolescence is characterized by physical, emotional, and psychological changes, including the onset of menstruation among adolescent girls. Appropriate personal hygiene practices are essential to prevent reproductive tract infections, urinary tract infections, and other health problems. However, such practices remain inadequate because of limited knowledge and access to reliable information. Data from the community health center in 2025 indicated that only 25% of adolescent girls in Kuranji Village understood the importance of changing sanitary pads every 4–6 hours, while a survey of 7 adolescent girls found that 5 had not practiced proper personal hygiene. This study aimed to determine the associations between knowledge level, information sources, and personal hygiene behavior during menstruation among adolescent girls in Kuranji Village in 2025. This quantitative study employed a cross-sectional design involving a population of 85 adolescent girls and a sample of 46 respondents selected through proportionate stratified random sampling. The inclusion criteria were adolescent girls aged 14–19 years who had experienced menstruation. Data were collected using questionnaires and analyzed through univariate and bivariate analyses using the chi-square test. The results showed that 23.9% of respondents had good knowledge, while 54.3% had access to good information sources. A significant association was found between knowledge and personal hygiene behavior, with a p-value of 0.001 (p < 0.05), as well as between information sources and personal hygiene behavior, with a p-value of 0.013 (p < 0.05). The Kuranji Village Government and Perampuan Community Health Center are therefore encouraged to provide structured, sustainable, and accessible reproductive health education for adolescents.